Measuring and modeling the fertility profile of indigenous people in Pakistan: A study of the Arians - Jamal Abdul Nasir; M. H. Tahir; Muhammad Riaz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
Because of no ethnographical survey, ecological and ethnographical studies are available in an underdeveloped area of demographic research in Pakistan. Keeping this view in mind, this paper evaluates the fertility profile of the Arians, an indigenous community in Pakistan. A random sample of 510 ever-married Arian women aged (15-49) years was selected from three districts in Pakistan where most of the Arian population lived. The analysis demonstrated that a minor proportion of Arians women 9.9% do not want to have another child while already they have no children. With the increase in the number of children and maternal age, the desire to have another child drops rapidly after age of 34 years among Arians women in Pakistan. Among all the women, average number of children considered ideal is lower than the average actual number of children. However, they prefer more sons than daughters and consider that there should be at least one male child in the family, revealing preference for son. Overall findings suggest that the fertility profile of Arians women was higher than their national counterparts. Modeling fertility rates is concerned to model fertility curves. Statistical modeling on the three distributions of fertility rates namely, age specific fertility rates, distribution of forward cumulative age specific fertility rates and distribution of backward cumulative age specific fertility rates was carried out. Finally, the cross-validity prediction power technique has been applied to check the validity of these models.
Keywords: 330; Age specific fertility rate; cross validity prediction power; demography; fertility; Punjabi Arians; reproductivity; statistical modelling